Modern approaches to the management of pregnancy in uterine myoma - I. F. Fatkullin; Y. V. Orlov; F. I. Fatkullin (Медицинский вестник Юга России, 2023)
The presented review summarizes current data on the tactics of accompanying patients with uterine myoma at various stages of their reproductive potential realization: the stage of pregravid preparation, the stage of pregnancy management, the moment of delivery and the postpartum period. Based on the analysis of domestic and foreign special scientific and practical literature, various methods of childbirth are proposed, from more preferable delivery through the natural birth canal, to the necessary caesarean section, performed strictly according to indications. Data are presented on the options for elective and emergency myomectomy during pregnancy, during operative delivery and in the postpartum period. Based on the results of systematization of the information received, the authors raise the question of the need for further research in the field of developing methods for optimal management of patients during pregnancy and childbirth complicated by uterine myoma, due to the relevance of the problems discussed.